Pemberdayaan Ekonomi Masyarakat Melalui Pembuatan Batu Bata Merah sebagai Usaha Produktif di Desa Montong Sapah Kabupaten Lombok Tengah - Hartawan Hartawan (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2025)
The purpose of this activity is to improve the community's economy through the manufacture of red bricks as a productive business in Kuwur Numpuk Hamlet, Montong Sapah Village, Central Lombok Regency. The methods applied are socialization and observation to the Regional Head. After the observation, interviews were conducted with partners, what are the problems that occur in the Kuwur Numpuk Hamlet community. From the existing problems and the solutions proposed, the partners finally accepted it very well with the description of the activities: 1) survey and cleaning the location is the initial work in the process of making red bricks, cleaning the location includes cleaning the location from trees/shrubs, grass, and garbage; 2) preparing materials such as clay, rice husks, water, and wood. This wood functions to burn red bricks; 3) making a hole for mixing the soil, then mix the clay with rice husks, mix with water; 4) crush the soil by trampling it until it becomes mud, on a fairly large scale you can use the help of animals such as buffalo. Don't let it be too soft (like porridge) because it won't be able to be molded; and 5) directly printed by putting a little ash in the mold so that it does not stick. When the clay is square like a brick, then drying is carried out. The results of the activities that have been carried out are from the entire process of making red bricks, the firing stage is the most decisive stage in determining the success or failure of this business. From the results of this activity, partners can produce red bricks so that they can reduce unemployment among the community, teenagers, parents, and adults.